Validation of a method for the quantitative determination of narcotic and psychotropic substances in urine by UHPLC–MS/MS - N. B. Savelieva; G. V. Ishutenko; A. V. Polosin; F. V. Radus; D. S. Polyansky; S. A. Kurbatkin; Yu. A. Efimova; P. V. Postnikov (Тонкие химические технологии, 2022)
Objectives. To validate a new method for the quantitative determination of 31 potent and narcotic substances and their metabolites in urine that meets the requirements of ISO/IEC 17025 using a fast and highly sensitive method of chromato-mass spectrometry with a view to introducing such a method into the routine practice of the National Anti-Doping Laboratory of the Lomonosov Moscow State University (NADL MSU).Methods. Urine samples soldered with standard solutions were analyzed using ultra high performance liquid chromatography-tandem mass spectrometry (UHPLC–MS/MS).Results. Diagnostic precursor/ion-product pairs and collision energies were established to allow unambiguous identification of the analyzed substances. During sample preparation, hydrolysis conditions were optimized. Selectivity, linearity, limits of qualitative determination, limit of quantitative determination (established under the contract with the customer firm), matrix effect, and measurement uncertainty were defined. Systematized data grouped by classes of analytes are given in the final table.Conclusions. The important advantages of the presented technique are the absence of complex and lengthy sample preparation, as well as the short time of the analysis method (about 10 min), which can significantly reduce duration along with labor and analysis costs. The addition of new analytes will ensure the versatility of the technique, as well as expanding its scope.